Calibrating visual sensors and actuators in distributed platforms - Hörster, Eva; Lienhart, R.; Kellermann, Walter; Bouguet, J. Y. (Computer Vision for Interactive and Intelligent Environments 2005, 2005)
Many novel multimedia, home entertainment, visual surveillance and health applications use multiple audio-visual sensors and actuators. In this paper we present a novel approach for position and pose calibration of visual sensors and actuators, i.e. cameras and displays, in a distributed network of general purpose computing devices. It complements our work on position calibration of audio sensors and actuators in a distributed computing platform [14]. The approach is suitable for a wide range of possible - even mobile - setups since (a) synchronization is not required, (b) it works automatically, (c) only weak restrictions are imposed on the positions of the cameras and displays, and (d) no upper limit on the number of cameras and displays under calibration is imposed. Corresponding points across different camera images are established automatically and found with subpixel accuracy. Cameras do not have to share one common view. Only a reasonable overlap between camera subgroups is necessary. The method has been sucessfully tested in numerous multi-camera environments with a varying number of cameras and displays and has proven itself to work extremely accurate. © 2005 IEE